Evaluation of The Website ‘Aisyiyah Surakarta of University Performance Based on Search Engine Optimization Using Automated Software Testing Gtmetrix - Aisyah Mutia Dawis; Ismail Setiawan (International Journal of Computer and Information System (IJCIS), 2022)
Each college would have definitely have a website, because in the world of Education, the website is very important in addition to as one of the supporting facilities for the needs of the information, the website also as a media promotion for each college. Therefore the performance of the website on higher education should be the most important thing due to one important role of a website in the support activities in a higher education. ’Aisyiyah Surakarta of University is one of the new university after previously named Stikes Aisyiyah Surakarta, therefore, the evaluation of the quality of the website conducted to determine the quality of the website using GTMetrix. The purpose of this study is to determine the performance of the website ‘Aisyiyah Surakarta of University as well as provide recommendations for improvement for the management of the website. Based on the test results obtained by the website located at grade E.This The results of testing the research evaluation of the performance of the website ‘Aisyiyah Surakarta of University can be concluded that the Performance Score with Page Speed in level E (56%) and Yslow at the level of E (53%).